ECTOMYCORRHIZAL MUSHROOMS DIVERSITY IN SORAYA RESEARCH STATION LEUSER ECOSYSTEM - Rahmadani, Ayu; Rasnovi, Saida; Ismail, Yulia Sari (Biotik, 2023)
Ectomycorrhizal macro fungi have a mutualistic symbiosis with several plants, including those from the Dipterocarpaceae, Myrtaceae, and Fagaceae families. The existence of ectomycorrhizal macro fungi in nature is very important to preserve, therefore this study was conducted to determine the diversity of ectomycorrhizal macro fungi at Soraya Research Station. This study aims to determine the diversity of ectomycorrhizal macro fungi at the Soraya Research Stasiun Subulussalam, Leuser Ecosystem Area. The study was conducted from August 2021 to January 2022. The research method used is an exploratory survey, sampling using the squared method, using a permanent phenological plot of 20 plots measuring 20 m x 20 m, which are randomly placed in the secondary forest of the Soraya Research Station. The results obtained consisted of 5 orders, 14 families, 31 species, and 1440 individual numbers of ectomycorrhizal macro fungi. The most numerous species are obtained from the Boletaceae family, which is 5 species, and the Russulaceae family is 4 species. The ectomycorrhizal macro fungi species diversity index is relatively moderate at 2,997.